2017
DOI: 10.1097/mlr.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Medicaid Home and Community-based Services Waivers on Unmet Needs Among Children With Autism Spectrum Disorder

Abstract: Background Several states have passed Medicaid Home and Community Based Services (HCBS) waivers that expand eligibility criteria and available services for children with autism spectrum disorder (ASD). Previous research has shown considerable variation in these waivers, but little is known about the extent to which they address the healthcare needs of children with ASD. Objective To determine the effects of Medicaid HCBS waivers, and their characteristics, on unmet healthcare needs among children with ASD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…We specified a multivariable logistic regression model that characterized the associations between unmet health care needs and HCBS waiver generosity, by race/ethnicity, controlling for other child characteristics (age, sex, and health status/whether the child was classified as having special health care needs), family characteristics (and household income), calendar year, and state‐level fixed effects. We specify the model as quasi‐difference‐in‐difference‐in‐difference (QDDD) model, where the first difference identifies changes in waiver status within states, the second identifies differences in those changes across states, and the third identifies differences by race/ethnicity. The QDDD model is a generalization of the standard difference‐in‐difference‐in‐difference model.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We specified a multivariable logistic regression model that characterized the associations between unmet health care needs and HCBS waiver generosity, by race/ethnicity, controlling for other child characteristics (age, sex, and health status/whether the child was classified as having special health care needs), family characteristics (and household income), calendar year, and state‐level fixed effects. We specify the model as quasi‐difference‐in‐difference‐in‐difference (QDDD) model, where the first difference identifies changes in waiver status within states, the second identifies differences in those changes across states, and the third identifies differences by race/ethnicity. The QDDD model is a generalization of the standard difference‐in‐difference‐in‐difference model.…”
Section: Methodsmentioning
confidence: 99%
“…Waiver generosity was characterized using the following three dimensions of waivers: (a) estimated cost, which each state calculates for its own waiver and is defined as the total annual estimated costs of waiver services per individual expected to participate in the waiver; (b) cost limit, defined as the maximum cost of services that each state allowed for individuals enrolled under the waiver; and (c) enrollment limit, defined as the maximum number of participants that the waiver will serve and expressed as a proportion of the total number of children in the state. 24 Each of the three measures was normalized by dividing by its standard deviation (SD), such that, after summing them to make a final generosity metric, they would have equal influence on that metric based on their empirical variation. The resulting generosity metric was normalized again by dividing by the mean generosity of waivers in the sample so that a value of 1 would represent the value of an average waiver and a value of 0 would reflect the absence of a waiver or a waiver for which the expected costs = the cost limit = the enrollment limit = 0.…”
Section: Primary Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Fifty current or former HCBS waivers in twenty-eight states and the District of Columbia include children with ASD in their target populations. Although previous studies have documented the considerable variation both within and between states in waiver characteristics 23 and have shown that waiver characteristics reduce unmet needs among children with ASD, 24 no studies have assessed waivers’ impact on parents’ workforce participation.…”
mentioning
confidence: 99%